The Reasonability of Using Complex Medical Prescriptions for Tumescent Anesthesia When Performing Endovenous Laser Obliteration of Varicose Veins - B. V. Kozlovskij; V. A. Arustamyan; I. P. Mikhaylov; A. M. Demyanov (Неотложная медицинская помощь, 2024)
INTRODUCTION. Despite the widespread use of methods for thermoobliteration of varicose veins, there are no standards for prescribing solutions for tumescent anesthesia when performing these operations. Existing prescriptions can be difficult, both in terms of finding the necessary components in a certain concentration, and in terms of correct dilution of the components in saline.   AIM OF STUDY. To determine the reasonability of using complex medicinal prescription solutions for tumescent anesthesia when performing endovenous laser obliteration of varicose veins of the lower extremities.   MATERIAL AND METHODS. The prospective study included 64 patients who underwent endovenous laser obliteration of the great or small saphenous vein. The operations were performed in accordance with the standard protocol on a device with a wavelength of 1,940 nm and radiation power from 5.0 to 6.0 W. Tumescent anesthesia was created using an automatic infiltration pump using 21 G needles with a length of 120 mm. Group I included patients (n = 34) who were anesthetized with a 0.1 % lidocaine solution at room temperature. Group II included patients (n = 30), for whom the anesthesia solution was prepared according to Klein’s standard prescription for tumescent anesthesia. The distribution of patients into groups was carried out using random sampling. Evaluation criteria: the presence or absence of complaints of pain during surgery and the level of pain assessed using a visual analogue scale.   RESULTS. The groups did not differ statistically significantly in terms of main clinical and demographic indicators (p < 0.05). Complaints of pain or burning during surgery were made by 2 patients (5.9 %) in group I and 5 patients (16.7 %) in group II (p = 0.0023). The average pain value according to the visual analogue scale in group I was 0.75 cm [0.30; 1.44], in group II – 1.85 cm [0.85; 2.72], p = 0.0017, while in group I the maximum number of patients — 24 (70.6%) were distributed in the range of 0–1 cm, in group II the maximum number of patients, 17 (56.7 %) were distributed in the range of 1.5–3 cm according to a visual analogue scale.   CONCLUSIONS. When using a simple 0.1 % lidocaine solution for tumescent anesthesia, a significantly lower average pain value according to VAS was obtained in comparison with the group of patients who used the standard D. Klein solution (0.75 cm and 1.85 cm, respectively, p = 0. 0017). Also, for the study group, a significantly lower frequency of perioperative complaints and complaints of severe pain was obtained (p < 0.01). The use of complex prescriptions of solutions for tumescent anesthesia when performing endovenous laser obliteration of varicose veins is impractical. The use of a simple 0.1 % lidocaine solution at room temperature, while following the surgical protocol, provides comfortable anesthesia.